2004
DOI: 10.1503/cmaj.1031189
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile-associated diarrhea in adults

Abstract: CLOSTRIDIUM DIFFICILE is the most important cause of nosocomial diarrhea in adults. Illness may range from mild watery diarrhea to life-threatening colitis. An antecedent disruption of the normal colonic flora followed by exposure to a toxigenic strain of C. difficile are necessary first steps in the pathogenesis of disease. Diagnosis is based primarily on the detection of C. difficile toxin A or toxin B. First-line treatment is with oral metronidazole therapy. Treatment with oral vancomycin therapy should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
287
2
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(306 citation statements)
references
References 106 publications
3
287
2
14
Order By: Relevance
“…Studies have shown that the rate of acquisition of such spores varies from 13% in patients with hospital stays of up to 2 weeks to 50% in stays longer than 4 weeks. [8] Accidental ingestion of C. difficile can result in either excretion of the bacteria in feces or asymptomatic colonization of the bacteria in the gut of the ingested person, or may result in disease with diarrhea termed as colitis or pseudomembranous colitis (PMN). Though C. difficile has been found in approximately 3% of normal adults and in up to 40% of hospitalized patients, [9] only about one -third of them develop colitis, whereas the rest remain asymptomatic where the microbe remains in a metabolically inactive spore form [10] and that it only becomes a problem after such carriers are treated with antimicrobial agents.…”
Section: Difficile Associated Diarrheamentioning
confidence: 99%
“…Studies have shown that the rate of acquisition of such spores varies from 13% in patients with hospital stays of up to 2 weeks to 50% in stays longer than 4 weeks. [8] Accidental ingestion of C. difficile can result in either excretion of the bacteria in feces or asymptomatic colonization of the bacteria in the gut of the ingested person, or may result in disease with diarrhea termed as colitis or pseudomembranous colitis (PMN). Though C. difficile has been found in approximately 3% of normal adults and in up to 40% of hospitalized patients, [9] only about one -third of them develop colitis, whereas the rest remain asymptomatic where the microbe remains in a metabolically inactive spore form [10] and that it only becomes a problem after such carriers are treated with antimicrobial agents.…”
Section: Difficile Associated Diarrheamentioning
confidence: 99%
“…Toxigenic strains of C. difficile produce two toxins which are responsible for a spectrum of clinical disease ranging from diarrhea to severe pseudomembranous colitis, toxic megacolon and ultimately death. C. difficile affects about 500 000 Americans each year, accounting for 15 000-20 000 deaths (Rupnik et al, 2009) with similar incidence reported in both Canada and Europe (Poutanen & Simor, 2004).…”
Section: Introductionmentioning
confidence: 56%
“…Aunque la administración antimicrobiana previa se ha demostrado en más de 95% de los pacientes inmunocompetentes con ICD, esta asociación se reduce a 80% en receptores de trasplante de órgano sólido. La reducción en la relación con exposición antimicrobiana puede ser secundaria a alteraciones en la microbiota normal y al deterioro de la inmunidad debido a inmunosupresores, enfermedad pre-trasplante grave e intervención quirúrgica 34,35 . La disfunción del sistema inmune es también un importan-te factor de riesgo en pacientes receptores de trasplante de órgano sólido.…”
Section: Poblaciones Especialesunclassified